ANALYSIS OF MARKETING MIX: Survey on PT Sinarmuda Setia Pertiwi Pekanbaru - Takbir Purbosari; Eka Komalasari (VALUTA, 2018)
Sinarmuda Setia Pertiwi Pekanbaru is a company engaged in property developers who directly plunge the spaciousness to do the construction up to sell housing products. Along with the development of modern times and high population growth more and more will demand for homes, with so arose similar companies that have the same profession. The problem is that the company is not yet able to achieve the sales target of housing products because there are still many consumers who canceled the purchase of housing, the higher prices offered for housing products so that many consumers to buy other products, as well as suspected prices of high housing products and quality housing Which is offered is not suitable and not worth the price caused the decline in demand for such housing. The type of research used is the type of quantitative research, namely research that emphasizes the analysis of numerical data (numbers) are processed with statistical methods, so that can be obtained the assessment of each variable. Methods of data collection is done by means of questionnaires (questionnaire), interviews, observation, and documentation. And using the census technique for sampling in 19 respondents. The operational variables of this study are Product, Price, Distribution / Place, Promotion. The results of this study of the four indicators are Good Enough. The author's suggestion is to improve the performance of the marketing department, especially in carrying out its function as the spearhead of a company in marketing the products sold by fixing the four variables that are considered less than the maximum.